Pengaruh Hedonic Shopping Motivation dan Shopping Lifestyle terhadap E-Impulse Buying Mahasiswi Universitas Negeri Padang pada Lazada.co.id - Widia Sefiska Rahma; Whyosi Septrizola (Universitas Negeri Padang, 2019)
This study aims to test and prove empirically the influence of hedonic shopping motivation and shopping lifestyle on e-impulse buying students at Padang State University at Lazada.co.id. The object of this study was students from Padang State University. The number of samples is as many as 100 respondents, the selection of samples using purposive sampling, which is the determination of the sample criteria ever bought at Lazada.co.id and do e-impulse buying. Hypothesis testing is done by using multiple regression analysis and tested using the SPSS version 16.0 application. The results of the study show that hedonic shopping motivation and shopping lifestyle have a positive and significant effect on e-impulse buying. Keywords: Impulse Buying, Hedonic Shopping Motivation, and Shopping Lifestyle